A Novel Service Broker Policy for e-Governance using Federation of cloud - Gupta, Ashutosh; Dhyani, Praveen; Rishi, OP; Pathak, Vishwambhar (International Journal of Computer Sciences and Engineering, 2025)
In the Federated cloud, the load balancing is a main challenge. It distributes uniformly dynamic load among multiple nodes in the distributed system environment. This makes any node not to be overloaded while the other nodes are idle or least load. The proper load balancing techniques improve the performance of cloud and utilize resource efficiently. The present study proposed Extended Performance Optimized Routing Policy service broker algorithm and compares it with the existing service broker algorithms in terms of response time and DC Processing time. The extended Performance Optimized Routing Policy service broker algorithm could be utilized in e-Governance framework that might help to develop the optimal and improved resource utilization. This possesses the scope to accelerate the e-Governance services and distribute the load at the peak hours.